‘Izz al-Dīn al-Zanjānī and His Scientific Contribution to Mathematics and Astronomy - GHERABA, Ouassila (Jordan Journal for History and Archaeology, 2023)
In this research paper, light is shed on unknown life of a forgotten mathematician. He achieved a fame through his writings and literary works that highlighted his scientific personality. He lived in a tense and dark period of Islamic history in Islamic East. This mathematician is ʿIzz al-Dīn al-Zanjānī, who lived in the first half of seventh century AH/ thirteenth century AD during Mongol invasion of Islamic East. We also try to enumerate his various works in mathematics and astronomy with their locations in different libraries of the world, and refer to books of his authorship that were attributed to others.